A Glomus Tumour of the Elbow: A Case Report and Review of the Literature. Issue 1 (January 2014) - Anley, Cameron; Vrettos, Basil; Roche, Stephen; Solomons, Michael
Extradigital glomus tumours are relatively uncommon. We present a case report of a glomus tumour of the elbow and review of the literature with regards to the clinical features, work-up and management of these tumours, to highlight the importance of considering a glomus tumour as part of the differential diagnosis in patient with atypical pain around the elbow.